Efficacy and Safety of High-dose Cholecalciferol in Patients With Inflammatory Bowel Disease Receiving Infliximab. Issue 4 (18th April 2022) - Gordon, Rebecca J.; Wells, Reeder; Johansen, Camille; Liu, Shanshan; Dahlberg, Suzanne E.; Snapper, Scott B.; Rufo, Paul A.
ABSTRACT: Objective: Vitamin D deficiency is prevalent in patients with inflammatory bowel disease (IBD). The goal of this study was to assess the efficacy and safety of high-dose, interval cholecalciferol administration in patients with IBD receiving infliximab. Methods: This prospective, longitudinal, open-label study enrolled pediatric and young adult patients with IBD and vitamin D deficiency. Subjects received 50, 000 IU every 4 to 5 weeks (n = 11) or 100, 000 IU every 6 to 8 weeks (n = 32) of oral cholecalciferol for 1 year. Dosing was directly observed and administered in conjunction with infliximab infusions. The primary endpoint was vitamin D sufficiency, defined as a 25-hydroxy-vitamin D (25-OHD) level ≥30 ng/mL. Results: Forty-three participants constituted the primary analysis population. 25-OHD levels reached steady-state after the third dose, and mean increases in 25-OHD levels were 8 vs. 4.5 ng/mL in the 100, 000 IU vs. 50, 000 IU treatment groups, respectively. Only 43.8% of patients receiving 100, 000 IU and 18.2% of patients receiving 50, 000 IU achieved sufficiency. There was no difference in the 25-OHD level responsiveness in patients with Crohn disease versus those with ulcerative colitis ( P = 0.72). There was no correlation between 25-OHD levels and clinical disease activity in patients with Crohn disease ( P = 0.85) or ulcerative colitis ( P = 0.24). Conclusions: Supplementation with cholecalciferol was well-tolerated and direct observation is a promising paradigm for ensuring compliance with therapy. Patients with IBD, however, appear to require high doses of cholecalciferol, with less than half of patients (37% overall) achieving vitamin D sufficiency. Additional studies are necessary to determine the optimal treatment regimens.